Study of the morphological alterations to enamel and dentin in human and bovine teeth after irradiation with Er : YAG laser - Fontana, C. R.; Malta, DAMP; Fontana, U. F.; Sampaio, JEC; Bernardes, V. L.; de Andrade, M. F. (Wiley-Blackwell, 2004)
Objective: the purpose of this study is to make use of scanning electron microscopy in order to comparatively analyze the morphological alterations to human and bovine enamel and dentin. Earlier data: Many a morphological study involving Er:YAG laser can be found in the literature. Still, not a single study comparing the effects of this infrared laser in human and bovine teeth has been reported. Materials and Methods: Thirty-two slices of human and bovine enamel and dentin were evenly divided into four groups. With the exception of the control group, the samples were irradiated with Er:YAG laser, focused at a distance of 12 mm and a 10-Hz frequency, with 150, 250, and 350 mJ of output energy per pulse for 10 seconds. After irradiation all specimens were observed under a scanning electron microscope. Results: There was practically no morphological difference for those samples that underwent 150 mJ/pulse irradiation. The dentin exposed to 250 mJ had a few open dentinal tubules. These were seen in enamel after a 350 mJ irradiation, in which the energy was able to reach the dentin. Conclusions: the breadth of this study allows us to state that the pattern between the species grew more heterogenous as the energy density was increased and that irradiation with 150 mJ/pulse resulted in greater likeness in human and bovine enamel and dentin.
Keywords: morphology; enamel; dentin; Er : YAG laser